The voices of Young New Zealanders Involved in Pediatric Palliative Care. Issue 3 (September 2013) - Gaab, Erin M.; Owens, R. Glynn; MacLeod, Roderick D.
The perspectives of young New Zealanders receiving pediatric palliative care (PPC) are not well understood. A qualitative study of the perceptions of 16 PPC patients and their siblings, aged 9 to 18, was conducted through audio and written diary accounts. Inductive thematic analysis revealed several concerns of participants, including special treatment that patients had received, spending time with their families, their feelings of being judged or discriminated against, their sense of being understood themselves and of understanding others, and mortality. A nonjudgemental, open approach is recommended when consulting with patients and their siblings in order to determine their needs.